Biomechanical Comparison of Two Conical Coupling Plate Constructs for Cat Tibial Fracture Stabilization - MacArthur, Sandra L.; Johnson, Matthew D.; Lewis, Daniel D. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective This study aimed to compare the biomechanical characteristics of two conical coupling plate (CCP) constructs in an ex vivo feline tibial fracture gap model.Study Design Paired tibiae harvested from eight recently euthanatized cats were alternately assigned to one of two stabilization groups. One tibia was stabilized with a standard, 6-hole, 2.5-mm CCP and the contralateral tibia was stabilized with a 6-hole, 2.5-mm prototype CCP (pCCP). Non-destructive cyclic four-point craniocaudal bending, mediolateral bending and axial compression testing were performed, and stiffness was recorded. The specimens were then loaded to failure in axial compression, and yield and failure loads were recorded.Results During non-destructive testing, the pCCP constructs were significantly stiffer than the CCP constructs in both modes of bending and axial loading. Both constructs demonstrated significantly greater craniocaudal bending stiffness compared with mediolateral bending. Yield load and failure load were significantly greater for the pCCP constructs.Conclusion The augmented design of the pCCP yielded superior mechanical characteristics during both non-destructive and destructive testings compared with constructs employing standard CCP. The more rigid design of the pCCP suggests that this implant may be better at withstanding greater loads, particularly when applied in a bridging fashion, during the postoperative convalescence. Further investigations are warranted to prospectively evaluate the clinical performance of the pCCP.
Keywords: locking plates; biomechanical; cat; tibial fracture; conical coupling